Level of adherence and associated factors to medication use in patients with diabetes mellitus - Mathar Mohideen Nagoor Thangam (Rev Rene)
Objective: to identify the level of medication adherence practices and associated factors among patients with diabetes mellitus. Methods: this cross-sectional descriptive study was conducted among diabetes mellitus patients at selected health centers in Tabuk, Saudi Arabia. A total of 218 participants were selected based on inclusion and exclusion criteria. The Medication Adherence Practice Scale with a maximum score of 50 was used to collect the data. Results: the mean medication adherence practice score was 28.64 ± 8.47, 65.1% of the participants had moderate adherence, 27.5% had high medication adherence, and 7.3% had low medication adherence. The multiple regression analysis showed that educational status (p=0.000), co-morbidity (p=0.001), monitoring of blood glucose (p=0.002), complications p=0.000), alternative therapies (p=0.000) and HbA1C level (p=0.000) were the significant predictors of medication adherence practice. Conclusion: this study identified the moderate medication adherence practices. Medication Adherence Practice was significantly associated with income, age, marital status, family size, educational status, occupation, years on diabetes medications, co-morbidity, medications for any other problems, number of antidiabetic drugs, source of medication adherence, regular monitoring, complications, and HbA1C level. Contributions to practice: studying the predictors of medication adherence practice of Diabetes Mellitus will enhance the health care interventions.